Troubleshooting Blow by Pressure High on the Komatsu Bulldozer Unit D375A-6R - Hasan Basri; Ery Diniardi; Anwar Ilmar Ramadhan (Journal of Applied Sciences and Advanced Technology, 2019)
PT United Tractors Tbk Loajanan-sanga site backs up a large number of customers, one of which is PT. RCI (RPP Contractors Indonesia) which is engaged in coal mining with the Komatsu D375A-6R unit which is used for dozzing and ripping. From the D375A-6R unit at PT. RCI experienced Troubleshooting on engines which caused Blow by pressure high, which resulted in the engine low power and could not run because the oil engine continuously exited from the oil engine filling hole, if the engine is forced to operate it is feared that the engine oil will run out and the engine components it will experience excessive wear and can also experience jammed which results in the maximum performance of the D375A-6R komatsu unit.